Ischiofemoral impingement due to a lipoma of the ischiofemoral space. (8th January 2016) - Papoutsi, Dimitra; Daniels, Jessica; Mistry, Alpesh; Chandraseker, Coonoor
Abstract : Non-focal hip and groin pain can frequently be a diagnostic problem, particularly if it is related to uncommon causes such as ischiofemoral impingement. The vast majority of published cases of ischiofemoral impingement are caused by osseous changes of the ischiofemoral interval. We describe an unusual case of ischiofemoral impingement caused by an intermuscular lipoma. Surgical resection of the tumour and histology confirmed the lipomatous nature of the tumour, with subsequent resolution of symptoms. To the best of our knowledge, this is the first case of a lipoma causing ischiofemoral impingement described in the English literature and emphasises that impingement can occur on the basis of a soft tissue mass occupying the interval of otherwise normal osseous interval and boundaries.